1977
DOI: 10.1128/aac.12.6.721
|View full text |Cite
|
Sign up to set email alerts
|

Structural Requirements of Guanide, Biguanide, and Bisbiguanide Agents for Antiplaque Activity

Abstract: The bactericidal efficacy of 16 guanide, biguanide, and bisbiguanide agents was studied in vitro against intact preformed plaques of four oral (plaqueforming) microorganisms: Streptococcus mutans, S. sanguis, Actinomyces viscosus, and A. naeslundii. The activities of these agents were examined in relation to their molecular configurations. These studies indicated that the bisand biguanide configurations are important for efficacy, as is the length of the alkyl side chain. No structural moiety determined effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
42
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 33 publications
1
42
0
Order By: Relevance
“…Accordingly, agents were tested here by short-term immersion of preformed plaques in various agents employing an in vitro preformed-plaque model system. The methods were previously detailed (30)(31)(32)(33). Briefly, in vitro plaques were rinsed free of broth in demineralized water and then immersed in 10 ml of aqueous solution of the various test or control agents, at pH 6.8 to 7.0, for various durations and frequencies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, agents were tested here by short-term immersion of preformed plaques in various agents employing an in vitro preformed-plaque model system. The methods were previously detailed (30)(31)(32)(33). Briefly, in vitro plaques were rinsed free of broth in demineralized water and then immersed in 10 ml of aqueous solution of the various test or control agents, at pH 6.8 to 7.0, for various durations and frequencies.…”
mentioning
confidence: 99%
“…PBI and CC. To employ a potential thera-X peutic utility index that could reflect the inteo gration of the effects of concentration, duration, and frequency of treatment required to achieve a bactericidal effect, the product of these parameters was computed for each of the five most t potent agents and for each of the test microorganisms and was expressed as a plaque bacteri-' cidal index (PBI) (32 Studies on the antiplaque activities of cationic detergents have been inconclusive with respect to their effectiveness against in vivo dental plaques (1,6,12,27,35). The studies of Sturzenberger and associates indicated that CPC (1.23 mM) or domiphen bromide (0.6 mM) used as adjuncts to tooth brushing effectively reduced amounts of bacterially undefined in vivo dental plaques as compared to a placebo tooth-brushing control (27).…”
mentioning
confidence: 99%
“…( Fig. 1) 10.0 g; beef heart infusion, 500 ml; yeast extract, 3.0 g; L-cystine, 0.25 g; sodium sulfite, 0.1 g; sodium thioglycolate, 0.5 g; sodium chloride, 7.5 g; glucose, 6.0 g; lactose, 5.0 g; and agar, 0.7 g [pH 7.2 + 0.1].) For experiments with S. mutans or S. sobrinus, a loopful of bacteria was inoculated into BHI broth and allowed to grow for 6 to 7 h at 37°C; and for experiments with Actinomyces species, 0.2 ml of bacterial suspension was inoculated into TF Medium for 24 h at 37°C for every experiment.…”
mentioning
confidence: 99%
“…For a long time, various compounds have been studied for possible use in plaque and caries control (4,12). Among these agents, chlorhexidine, a bisbiguanide compound, has been shown to exert antimicrobial and/or antiplaque effects (10). In addition, some cationic detergents such as cetylpyridinium chloride have been investigated for the same purpose (1,11).…”
mentioning
confidence: 99%
“…Cultures were stored either lyophilized or frozen (-70°C). Experimental working culture stocks were maintained by passage twice monthly in fluid thioglycolate medium containing 20%o (vol/vol) meat extract and excess CaCO3 (17).…”
mentioning
confidence: 99%